Influence of Dietary Zinc, Copper, and Manganese on the Intestinal Health of Broilers Under Eimeria Challenge - Bortoluzzi, Cristiano; Vieira, Bruno Serpa; Applegate, Todd Jay (Frontiers in Veterinary Science, 2020)
The incidence of enteric infections in broiler chickens may increase worldwide due to mounting pressure to limit the use of sub-therapeutic antibiotics and ionophores for coccidia suppression/prevention in the diets of broilers. For this reason, we need expand our knowledge on the role that micro-minerals have in modulating the intestinal physiology, immunology and microbiology of broiler chickens. There are issues associated with the use of high doses of some micro-minerals in the diets of animals, such as environmental contamination, bacterial resistance, and gizzard erosion. Therefore, there is a need to maximize the absorption of these minerals by the gastrointestinal tract (GIT) of birds when intestinal function may be compromised. Zinc is an essential micromineral required for growth, and influences intestinal development and/or regeneration during and after enteric disease. Two studies were conducted by our lab to determine the effects of Zn source in broilers under coccidia and Clostridium perfringens challenge. In the first study, Zn proteinate had beneficial effects on the performance of chickens challenged with coccidia plus C. perfringens by enhancing intestinal integrity and partially attenuating the inflammatory response. In the second study, Zn proteinate lowered the expression of pro-inflammatory cytokines and modulated the ileal microbiota. Additionally, the poultry industry has used prophylactic concentrations of dietary Cu for its ability to improve feed conversion for a long time. Copper absorption occurs mainly in the duodenum of chickens and, therefore, injuries to the intestinal epithelium of duodenum would impair Cu absorption and decrease its tissue concentration. Although there is a lack of studies relating Mn supplementation and its different sources on the immune response against coccidiosis in poultry, it is likely that Mn is beneficial during enteric challenges due to its role in the production of mucopolysaccharides. Therefore, the proper evaluation of the role of minerals on mitigating the negative impact of coccidiosis in broilers must consider their properties in modulating the physiology, immunology, and the intestinal microbiota of the host during health and disease situation events.